KONSTRUKSI GENDER LAKI-LAKI HOMOSEKSUAL DALAM SERIAL TELEVISI QUEER AS FOLK - Primiani, Nurrahma; Zakaria, Mumuh Muhsin; Priyatna, Aquarini (Capture : Jurnal Seni Media Rekam, 2017)
This study entitled â€œGender Construction on Homosexual Men in Television Series â€˜Queer as Folkâ€™â€ investigates how gender on homosexual men is portrayed and constructed in various scenes and dialogues depicted in the television series. By taking the discourse of [homo]sexual practice and fashion, homosexual men are shown to have different gender roles on each occasion. It is performed by them to survive, both in their homosexual community and in [hetero]normative neighborhood. This article argues that homosexual men at the same time are shown to perform by following two different standards. The data used in this study are textual and visual data (screenshots) captured from the series. After analyzing the data, this study finds non-normative gender views performed by homosexual men which tied and related to [hetero]normative gender roles.Key words: Homosexual, gender, heteronormativity, and Queer As Folk